Morphologic analysis and Neotype designation of the Raspthorn sandskate, Psammobatis scobina, from its type locality (Revista de Biología Marina y Oceanografía, 2022)
The genus Psammobatis is endemic to South America, and three of its species are sympatric along the Chilean coast. Their morphological similarity as well as the lack of type material of P. scobina, has made its taxonomic identification especially complex. The aim of this work is to allow for objective identification and comparisons of P. scobina, providing a new morphological characterization, incorporating both morphometric and meristic features for both sexes, and designating a Neotype. Morphometric and meristic data are presented separately for the Neotype, and for males and females to determine variability between sexes. Although there is overlap between some morphometric features of males and females, there are also some morphometric measures that differed between sexes among specimens of similar sizes, such as disc width, length of posterior pelvic lobe, preoral length, distance between fifth gill slits and distance from cloaca to second dorsal fin. Additionally, Principal Component Analysis and cluster analyses allowed to identify sexual dimorphism in specimens, with the most influential variables related to tail length. There are several unresolved issues regarding the taxonomy of this problematic genus, especially those regarding P. scobina and P. normani, which are sympatric in the southeastern Pacific. In addition to the analysis of skeletal structures and egg cases, an integrative comparative morphometric analysis, based on a recent standardized methodology with the inclusion of both morphological and molecular data, is still needed. The designation of a Neotype for objective comparative purposes, will allow such future study.